2021
DOI: 10.3389/fmed.2021.740154
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytomegalovirus Infection With Anti-MDA5 Antibody-Positive Dermatomyositis: A Prospective Cohort Study

Abstract: Objectives: To investigate whether cytomegalovirus (CMV) infection plays a role in the pathogenesis and prognosis of idiopathic inflammatory myopathy (IIM), particularly in anti-MDA5 antibody-positive (anti-MDA5+) dermatomyositis (DM).Methods: A prospective cohort of 204 newly diagnosed IIM patients and 50 healthy individuals were enrolled in the study. CMV-IgM and CMV-IgG antibody concentrations and lymphocyte counts were analyzed. Differences in categorical data were compared using Fisher's exact test and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…Huang et al. reported that CMV infections were significantly higher in idiopathic inflammatory myopathy patients, particularly in MDA5+ DM patients, and suggested that CMV might participate in the pathogenesis of MDA5+ DM by decreasing CD4+ T cells and CD19+ B cells ( 4 ). Our previous studies have also reported the high incidence of EBV and CMV infections, and found that the Th17 and Treg levels were decreased in the SLE patients with EBV or CMV viremia ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al. reported that CMV infections were significantly higher in idiopathic inflammatory myopathy patients, particularly in MDA5+ DM patients, and suggested that CMV might participate in the pathogenesis of MDA5+ DM by decreasing CD4+ T cells and CD19+ B cells ( 4 ). Our previous studies have also reported the high incidence of EBV and CMV infections, and found that the Th17 and Treg levels were decreased in the SLE patients with EBV or CMV viremia ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate of CTD such as systemic lupus erythematosus and dermatomyositis is high and there is no current cure. The main therapeutic strategies are glucocorticoids and immunosuppressive drugs, but the effects are not satisfactory and the side effects are obvious, leading to the increase of infection ( 2 4 ). Autoimmune disorders and treatments give rise to susceptibility for infections in CTD, it is reported that the risk of opportunistic infection was highest for dermatomyositis and polymyositis/dermatomyositis (DM/PM), followed by systemic lupus erythematosus (SLE) ( 2 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Viral infection has long been thought to be a potential etiology for autoimmune disease, including IIM [ 1 , 3 , 12 , 27 ]. Development of autoimmune reaction following SARS-CoV-2 infection (including IIM) has been described extensively and the similarities with anti-MDA5 disease and COVID-19 infection have further increased this suspicion [ 1 , 2 , 4 , 12 – 15 , 28 35 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…This sets the tone for the suggestion that the production of anti-MDA5 antibodies during virus infection, including COVID-19, is an epiphenomenon associated with the onset of CADM and RP-ILD; namely, infection of the skin and lung epithelium that may up-regulate the expression of MDA5 in the infected tissues [ 1 3 , 17 , 36 , 39 ]. The possible mechanisms of autoimmunity may be molecular mimicry, or the virus itself may activate antigen-presenting cells directly, activation of T-cells, and consequent cytokine storm with resultant tissue damage [ 13 , 27 ]. This can further be favored by specific genetic variants predisposing individuals to loss of tolerance of the MDA5 antigen resulting in the production of anti-MDA5 autoantibodies [ 3 , 39 , 40 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation